FTY720 ameliorates renal fibrosis by simultaneously affecting leucocyte recruitment and TGF-β signalling in fibroblasts. (27th July 2017) - Tian, T; Zhang, J; Zhu, X; Wen, S; Shi, D; Zhou, H
Summary: Renal fibrosis is the common final manifestation of chronic kidney diseases and usually results in end-stage renal failure. In this study, we evaluated the effect of fingolimod (FTY720), an analogue of sphingosine 1-phosphate (S1P), as a treatment for the unilateral ureteral obstruction (UUO)-induced renal fibrosis animal model. We treated mice with FTY720 at a dosage of 1 mg/kg/day by intragastric administration from day 1 until day 7. The control group received the same amount of saline. FTY720 reduced significantly the urine albumin/creatinine ratio (UACR) in treated UUO mice. FTY720 treatment also caused a significant decrease in interstitial expansion and collagen deposition in the kidney, accompanied by reduced mononuclear cell recruitment and inflammatory cytokine expression. In addition, the expression levels of the endothelial cell adhesion molecules P-selectin and vascular cell adhesion protein 1 (VCAM-1) were suppressed in the ligated kidney by FTY720 administration, suggesting reduced renal endothelial cell activation. Furthermore, in renal interstitial fibroblast normal rat kidney (NRK)-49F cells, FTY720 significantly affected transforming growth factor (TGF)-β-induced α-smooth muscle actin (SMA) expression and collagen synthesis by inhibiting both the Mothers against decapentaplegic homologue (Smad)2/3 and phosphatidylinositol 3-kinase/protein kinase B/glycogen synthase kinase 3 beta (PI3K/AKT/GSK3β) signalling pathways. S1P1 knock-down by siRNA reversed this effect significantly in our fibroblast cell culture model. Therefore, FTY720 attenuates renal fibrosis via two different mechanisms: first, FTY720 suppresses the synthesis of extracellular matrix in interstitial fibroblasts by interfering with TGF-β signalling; and secondly, FTY720 affects endothelial cell activation and chemokine expression, thereby reducing immune cell recruitment into the kidney. Graphical Abstract: